2016
DOI: 10.7454/mss.v20i2.5948
|View full text |Cite
|
Sign up to set email alerts
|

Photoproduction of π0-Mesons from the Nucleon and Deuteron

Abstract: The photoproduction of π 0 -mesons from the nucleon and deuteron has been studied for incidents of photon energies up to 1.5 GeV. By using the MAID-2007 model for the process on the nucleon, we predict results for the unpolarized and helicity-dependent total cross sections of the semi-exclusive reaction γd→π 0 X (X=np+d) with the inclusion of rescattering effects. We find that rescattering effects yield a substantially large contribution. The extracted results are compared with the available experimental data … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…To conclude this section, although the present models yield different contributions to the GDH sum rule, the small contribution of KΣ channels implies that the contribution of pion and two-pion channels should be larger than those predicted by previous calculations [7][8][9]. Otherwise, we need to search for additional contributions, e.g.…”
Section: Contribution Of the Kς Channels To The Gdh Sum Rulementioning
confidence: 75%
See 2 more Smart Citations
“…To conclude this section, although the present models yield different contributions to the GDH sum rule, the small contribution of KΣ channels implies that the contribution of pion and two-pion channels should be larger than those predicted by previous calculations [7][8][9]. Otherwise, we need to search for additional contributions, e.g.…”
Section: Contribution Of the Kς Channels To The Gdh Sum Rulementioning
confidence: 75%
“…For the sake of comparison with the previous calculations, instead of using equation (55) we use the definition of GDH integral Obviously, the largest contribution to the photoabsorption cross sections originates from the pion and two-pion photoproductions since the corresponding cross sections are almost two order of magnitude larger than that of kaon photoproduction. However, as shown in [7][8][9], equation (55) would be convergent if the contribution of kaon photoproduction on the proton was nearly +4 μb. It is shown in [5,6] that the contribution of Kaon-Maid for the proton anomalous magnetic moment is 2.93 μb, where the contribution of both K + Σ 0 and K 0 Σ + channels is 1.68 μb.…”
Section: Contribution Of the Kς Channels To The Gdh Sum Rulementioning
confidence: 98%
See 1 more Smart Citation
“…Since the pioneering work of Chew, Goldberger, Low and Nambu [3], extensive work during more than fifty years has shown that, below 0.45 GeV incident photon energy, the dominant mechanisms of the N N g p  reaction are the background and the Δ-resonant excitation. After that, high efforts have been carried out both experimentally (see for π and [31][32][33][34][35][36][37][38][39][40][41] for η-photoproduction and references therein) and theoretically (regarding π photoproduction see for example models developed in [42][43][44][45][46][47][48][49][50][51][52][53], MAID model [54][55][56], Bonn-Gatchina model [57,58], chiral Lagrangian based models [59][60][61], quark model [62], and [63][64][65] for η-photoproduction) to study the cross sections of π and η mesons photoproduction reactions, arriving in the present to higher incident photon energies of the order of 1.2 GeV. By this reason, to obtain a good theoretical description of the experimental data we need: (i) to add to the Δ resonance the contribution of those ones belonging to the second resonance region; and (ii) to perform a consistent description of the Δ resonance, nondivergent at energies well above its peak.…”
Section: Introductionmentioning
confidence: 99%